Metal enrichment of soils in three urban drainage grass swales used for seasonal snow storage - Gavrić, Snežana; Leonhardt, Günther; Österlund, Heléne; Marsalek, Jiri; Viklander, Maria (The Science of the total environment, 2021)
Enrichment of soils in three urban drainage swales by metals associated with traffic sources was investigated in a cool temperate climate with seasonal snow. Such swales differed from those not exposed to snow by receiving additional pollutant loads from winter road maintenance involving applications of salt and grit, use of studded tires, and storage and melting of polluted snow cleared from trafficked areas into swales. Among the swales studied, swale L2 in the downtown was the oldest (built around 1960), drained runoff from a road with the highest traffic intensity, and exhibited the highest mean concentrations of most of the metals studied (Pb, Cu, Zn, Cr, Cd, Ni, Co, V, Ti, and W). In the case of Pb, this exceedance was about an order of magnitude: 71 mg/kg DW in L2, compared to about ~8 mg/kg DW in L1 and L3, both built in 1979. Among the metals originating from local geology, barium (Ba) was found in the swales and the grit material at high concentrations of ~650 mg/kg DW and 700–1000 mg/kg DW, respectively. Such concentrations exceeded the Swedish EPA guideline limits of 300 mg/kg DW for less sensitive soil use. The sequential extraction analysis of samples from swale L2 indicated that Ba was mostly in the immobile residual fraction (90%). The absence of clear decline in metal concentrations with distance from the trafficked surfaces suggested that stored snow was another source of metals partly balancing spatial distribution of metals in swale soils. [Display omitted] •Good infiltration rates of native swale soils after 40–60 years of operation.•Stormwater runoff from trafficked areas is a source of metals in swale soils.•Snow with grit, cleared from pavements, largely ends up and melts in swales.•High levels of residual Barium in swale soils were attributed to local geology.